Correlation between sleep disorder screening and executive dysfunction in children with attention deficit-hyperactivity disorder - Zambrano-Sanchez,Elizabeth (2013)
Objective To compare frequency of sleep disorders (SD) and executive dysfunction (ED) in children with attention deficit-hyperactivity disorder (ADHD) and a control group. Method We studied 156 children with ADHD with a mean age of 8.5 years, and a control group with 111 children with a mean age of 8.3 years. We utilized the Pediatric Sleep Questionnaire (PSQ) to screen SD and the working memory measurement from the Wechsler intelligence scale for children (WISC-IV) to screen ED. Results We did not observe an increased frequency of SD in children with ADHD compared with the controls. However, we did identify ED in children with ADHD; additionally a significant correlation was observed between the type of ADHD and SD and among ED, WISC-IV measurements, and type of SD in children with ADHD. Conclusion An increase of SD frequency in children with ADHD was not observed, but we did identify ED in children with ADHD. Additionally, a correlation among ADHD types, SD, ED, and WISC-IV measurements was observed in children with ADHD.